2018
DOI: 10.1029/2018ja026081
|View full text |Cite
|
Sign up to set email alerts
|

The Transition Between Antiparallel and Component Magnetic Reconnection at Earth's Dayside Magnetopause

Abstract: Magnetic reconnection at Earth's magnetopause is usually described by two different scenarios, antiparallel and component reconnection. The Maximum Magnetic Shear model combines these two scenarios at specific connection points known as the Knee regions. Using a database of confirmed magnetopause reconnection locations observed during Phase 1a of the Magnetospheric Multiscale mission, a recent study showed that the model predicts the reconnection locations correctly within 2 Earth radii 80% of the time. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Here we use the maximum magnetic shear model by Trattner et al () to estimate the possible source region of FTE cascades. The FTE cascades in our study appear during those IMF conditions (southward IMF with a strong B y component) for which the maximum magnetic shear model gives an excellent agreement with observations of normal reconnection events (Trattner et al, , , , ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here we use the maximum magnetic shear model by Trattner et al () to estimate the possible source region of FTE cascades. The FTE cascades in our study appear during those IMF conditions (southward IMF with a strong B y component) for which the maximum magnetic shear model gives an excellent agreement with observations of normal reconnection events (Trattner et al, , , , ).…”
Section: Discussionsupporting
confidence: 89%
“…These include, according to Trattner et al (2012), pure southward IMF and dominant IMF B x cases (the model predicts in those cases only reconnection along bifurcated antiparallel reconnection regions, which could not be confirmed observationally) and equinox and midwinter cases with IMF clock angles around 140°and 240° (Trattner et al, 2017). As shown in Trattner et al (2018), the equinox and midwinter deviations disappear when extending the antiparallel reconnection regions to include all field lines that contain antiparallel reconnection somewhere along the field lines. The model deviation from observations for pure southward and dominant B x with observations still needs to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The models used in this study require the upstream solar wind observations as input parameters to create magnetic shear angle plots for the magnetopause. To determine the correct solar wind convection times to the magnetopause for the upstream observations by the Wind satellite (Lepping et al, 1995; Ogilvie et al, 1995), solar wind magnetic field rotations observed at the Wind satellite are individually lined‐up with the magnetosheath magnetic field rotations observed by MMS/FGM (e.g., Trattner, Burch, et al, 2017; Trattner et al, 2018).…”
Section: Observationsmentioning
confidence: 99%
“…In the dawn sector, the anti‐parallel reconnection region is located in the northern hemisphere and extends straight toward the northern cusp. In the dusk sector, the anti‐parallel reconnection region is wrapped around both hemispheres, creating a shape resembling a “Hook” (e.g., Trattner et al, 2018), before extending to the southern cusp region. The white line crossing the dayside magnetopause represents the location of the predicted component reconnection tilted X‐line based on the maximum magnetic shear model.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation